Self-healing injectable photo-crosslinking dual-network hydrogel and preparation method thereof

By performing methacrylation modification and dextran oxidation treatment on silk fibroin, a dual network hydrogel was formed, which solved the problems of poor gel-forming performance and low biocompatibility of existing hydrogels, and achieved self-healing, good mechanical properties and high safety effects.

CN119798715AActive Publication Date: 2025-04-11HAINAN UNIV

Patent Information

Application Number
CN202510042703.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-11
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

The existing medical silk fibroprotein hydrogels have problems such as excessive holes, poor gel-forming performance, long time, poor adhesion, poor mechanical properties, and easy to break after formation. The residual chemical crosslinking agent leads to toxicity and reduces biocompatibility.

Method used

Silk fibroprotein is modified by methacrylation, double bonds are introduced, and dextran is oxidized by sodium periodate, aldehyde group is introduced, forming a Schiff base cross-linking reaction, forming a double network hydrogel, improving its structural density and performance.

Benefits of technology

The hydrogel has achieved self-healing, good mechanical properties, high safety and biocompatibility, and has both injectability and sustained release after drug loading.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798715A_ABST
    Figure CN119798715A_ABST
Patent Text Reader

Abstract

The invention discloses a self-healing injectable photo-crosslinking dual-network hydrogel and a preparation method thereof.The preparation method comprises the steps that silk fibroin is subjected to methacrylation modification through a glycidyl methacrylate solution, then dextran of the silk fibroin is subjected to an oxidation reaction through a sodium periodate solution, oxidized dextran is generated, and the self-healing injectable photo-crosslinking dual-network hydrogel is obtained; the amino group in the modified silk fibroin and the aldehyde group of the oxidized dextran are subjected to a Schiff base cross-linking reaction to form the double-network hydrogel. The hydrogel with the double-network structure prepared by the invention is more compact in structure, so that the hydrogel has a series of excellent performances such as injectability, relatively good adhesion, good mechanical property, self-healing property and slow release property after drug loading while having safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomaterials, and in particular to a self-healing, injectable photo-crosslinked double-network hydrogel and a preparation method thereof. Background Art

[0002] Wound healing is a highly organized biological process, which mainly includes four typical overlapping stages: hemostasis, inflammation regulation, cell proliferation and tissue remodeling. However, due to the special local microenvironment of diabetic wounds, such as long-term inflammation, poor angiogenesis and epithelial dysfunction, diabetic wounds can heal slowly or even fail to heal, which may lead to amputation or even threaten life safety.

[0003] At present, the main means of wound treatment for diabetic patients include wound dressings, hyperbaric oxygen therapy, negative pressure wound therapy, growth factor-based therapy and stem cell therapy. However, except for wound dressings, the other methods have problems such as high cost, instability and lack of certain safety evaluation methods. Therefore, wound dressing therapy is still the main treatment method.

[0004] The most promising medical dressing at present is hydrogel. As a hydrophilic three-dimensional cross-linked network system, hydrogel has multiple advantages in medical dressings. Injectable hydrogel has more obvious advantages in wounds and other diseases due to its shear-thinning properties, adjustable physical and chemical properties, controllable degradation performance, high water content and ability to deliver in a minimally invasive manner. At present, it has important research and application value in the fields of cell 3D culture, wound dressing, drug delivery, tissue engineering, regenerative medicine, etc.

[0005] Silk fibroin is a natural polymer protein extracted from silk. It has biocompatibility and biodegradability. It is composed of fibroin and sericin. Fibroin includes a hydrophobic peptide chain (H chain) and a hydrophilic peptide chain (L chain). The special amino acid sequences of the H chain and the L chain enable it to form a variety of protein secondary conformations. The various properties of silk fibroin materials can be effectively controlled by regulating the secondary structure of silk fibroin. Silk fibroin produced by silkworms has been approved by the FDA for drug delivery and surgical suture applications. Due to its excellent biocompatibility, adjustable biodegradability and mechanical properties, it has been used in various biomedical applications.

[0006] At present, in order to improve the shortcomings of single-network hydrogel composed of silk fibroin, such as large pores after forming hydrogel, poor gelation performance, long time, poor gel adhesion, poor mechanical properties, easy breakage, etc., the main improvement method is to add chemical crosslinking agents. Although this method can enhance the performance of hydrogel, due to the residual chemical crosslinking agents, it brings certain toxicity, thereby reducing the biocompatibility of hydrogel. Therefore, it is necessary to develop a safe, non-toxic medical dressing with good gelation performance and mechanical properties to increase its practicality. Summary of the invention

[0007] Therefore, the object of the present invention is to provide a self-healing, injectable photo-crosslinked double network hydrogel and a preparation method thereof, wherein the hydrogel has good self-healing properties, better mechanical properties and higher safety.

[0008] The above object of the present invention is achieved through the following technical solutions:

[0009] One aspect of the present invention provides a method for preparing a self-healing, injectable photo-crosslinked double network hydrogel, comprising the following steps:

[0010] (1) Preparation of modified silk fibroin

[0011] The degummed silk fibroin fibers are dissolved in a lithium bromide aqueous solution, stirred and dissolved at a temperature of 65°C, and a glycidyl methacrylate solution is added dropwise while stirring to perform methacrylation modification, and stirred for 5 to 8 hours to obtain a mixed solution, and the mixed solution is dialyzed and freeze-dried to obtain a sponge-like modified silk fibroin;

[0012] (2) Preparation of oxidized dextran

[0013] Dextran is added to deionized water, and then sodium periodate solution is dripped into the dextran solution, stirred at room temperature in the dark for 3 to 6 hours, and then ethylene glycol is added to stop the reaction, followed by dialysis and freeze-drying to obtain oxidized dextran;

[0014] (3) The oxidized dextran solution is mixed with the modified silk fibroin solution, and then a photoinitiator solution is added to obtain a sol, and a photo-crosslinked double network hydrogel is obtained by irradiating the sol with ultraviolet light.

[0015] In an optional embodiment, the mass ratio of the silk fibroin fiber to the glycidyl methacrylate is 10:3.

[0016] In an optional embodiment, the mass ratio of the dextran to the sodium periodate is 2.5:1.

[0017] In an optional embodiment, the mass ratio of the modified silk fibroin to oxidized dextran is 3:(0.5-9).

[0018] In an alternative embodiment, the oxidation substitution degree of the oxidized dextran is 20%.

[0019] In an optional embodiment, the method for preparing a photo-crosslinked double network hydrogel according to claim 1 is characterized in that in the step (1), the concentration of the lithium bromide aqueous solution is 8 to 10 mol / L; the concentration of the glycidyl methacrylate solution is 300 to 400 mmol / L.

[0020] In an optional embodiment, in step (2), the mass concentration of the sodium periodate solution is 20%.

[0021] In an optional embodiment, in step (3), the mass volume concentration of the modified silk fibroin aqueous solution is 10-20%; the mass volume concentration of the oxidized dextran aqueous solution is 5-10%.

[0022] In an optional embodiment, in step (3), the mass volume concentration of the photoinitiator solution is 0.1-0.2%.

[0023] Another aspect of the present invention is to provide a photo-crosslinked double network hydrogel, which is prepared by the above-mentioned preparation method.

[0024] Compared with the prior art, the technical solution of the present invention has the following advantages:

[0025] The present invention first performs methacrylation modification on silk fibroin to introduce double bonds to improve its solubility, then performs oxidation treatment on dextran with sodium periodate to introduce aldehyde groups, and after the modified silk fibroin and oxidized dextran are mixed, the amino groups in the modified silk fibroin and the aldehyde groups of the oxidized dextran undergo Schiff base cross-linking reaction to form a double network hydrogel, making the hydrogel structure denser, so that the hydrogel has a series of excellent properties such as injectability, good adhesion, good mechanical properties, self-healing properties and sustained-release properties after drug loading, while having safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a picture of the photo-crosslinked double network hydrogel of the present invention;

[0027] Figure 2 The SEM photos of the hydrogels provided in the embodiments and comparative examples of the present invention after vacuum freeze-drying;

[0028] Figure 3 A picture showing that two hydrogels provided by an embodiment of the present invention can heal each other;

[0029] Figure 4 This is a picture of the hydrogel provided by an embodiment of the present invention being injected into water;

[0030] Figure 5 The rheological behavior of the hydrogel provided by the embodiment of the present invention;

[0031] Figure 6 The rheometer behavior of dextran with different oxidation substitution degrees and silk fibroin mixed at different mass ratios according to the present invention;

[0032] Figure 7 The hemolytic activity of the hydrogel provided by the embodiment of the present invention. DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0034] Example 1

[0035] (1) Preparation of modified silk fibroin

[0036] Take silkworm cocoons, cut them into pieces, add 2L of 5g / L Na2CO3 aqueous solution into the induction cooker, soak the cut silkworm cocoons in it, boil them slightly for 30 minutes, then soak and rinse them with a large amount of deionized water at least five times, repeat the above operation three times, wring them out, tear them into strips, and place them in a 37°C oven to dry to obtain degummed silk fibroin fibers.

[0037] Use a volumetric flask to make up the volume, prepare 50mL of 9M (40g) lithium bromide aqueous solution, take 10g of degummed silk fibroin fiber and dissolve it in the lithium bromide aqueous solution, stir and dissolve at a temperature of 65°C, while stirring, drop 2.5mL (350mM) glycidyl methacrylate solution to perform methacrylation modification, stir for 6h to obtain a mixed solution, dialyze the mixed solution, and freeze-dry to obtain a sponge-like modified silk fibroin;

[0038] (2) Preparation of oxidized dextran

[0039] 2.5 g of dextran was added to 50 mL of deionized water to obtain a dextran solution, and then 5 mL (20% w / v) of sodium periodate solution was dropped into the dextran solution, stirred for 4 h at room temperature in the dark, and then 2 mL of ethylene glycol was added to stop the reaction, followed by dialysis and freeze-drying to obtain oxidized dextran, wherein the oxidized dextran has an oxidative substitution degree of 20%;

[0040] (3) 5 mL (10% w / v) of oxidized dextran solution was mixed with 10 mL (15% w / v) of modified silk fibroin solution, and then 10 mg of 0.1% LAP (phenyl (2,4,6-trimethylbenzoyl) lithium phosphate) was added to mix to obtain a sol, and a photo-crosslinked double network hydrogel was obtained by ultraviolet light irradiation.

[0041] Example 2

[0042] (1) Preparation of modified silk fibroin

[0043] Take silkworm cocoons, cut them into pieces, add 2L of 5g / L Na2CO3 aqueous solution into the induction cooker, soak the cut silkworm cocoons in it, boil them slightly for 30 minutes, then soak and rinse them with a large amount of deionized water at least five times, repeat the above operation three times, wring them out, tear them into strips, and place them in a 37°C oven to dry to obtain degummed silk fibroin fibers.

[0044] Use a volumetric flask to make up the volume, prepare 50mL of 9M (40g) lithium bromide aqueous solution, take 10g of degummed silk fibroin fiber and dissolve it in the lithium bromide aqueous solution, stir and dissolve at a temperature of 65°C, while stirring, drop 2.5mL (350mM) glycidyl methacrylate solution to perform methacrylation modification, stir for 6h to obtain a mixed solution, dialyze the mixed solution, and freeze-dry to obtain a sponge-like modified silk fibroin;

[0045] (2) Preparation of oxidized dextran

[0046] 2.5 g of dextran was added to 50 mL of deionized water to obtain a dextran solution, and then 5 mL (20% w / v) of sodium periodate solution was dropped into the dextran solution, stirred for 4 h at room temperature in the dark, and then 2 mL of ethylene glycol was added to stop the reaction, followed by dialysis and freeze-drying to obtain oxidized dextran, wherein the oxidized dextran has an oxidative substitution degree of 20%;

[0047] (3) 15 mL (10% w / v) of oxidized dextran solution was mixed with 10 mL (15% w / v) of modified silk fibroin solution, and then 10 mg 0.01% LAP (phenyl (2,4,6-trimethylbenzoyl) lithium phosphate) was added to mix to obtain a sol, and a photo-crosslinked double network hydrogel was obtained by ultraviolet light irradiation.

[0048] Example 3

[0049] (1) Preparation of modified silk fibroin

[0050] Take silkworm cocoons, cut them into pieces, add 2L of 5g / L Na2CO3 aqueous solution into the induction cooker, soak the cut silkworm cocoons in it, boil them slightly for 30 minutes, then soak and rinse them with a large amount of deionized water at least five times, repeat the above operation three times, wring them out, tear them into strips, and place them in a 37°C oven to dry to obtain degummed silk fibroin fibers.

[0051] Use a volumetric flask to make up the volume, prepare 50mL of 9M (40g) lithium bromide aqueous solution, take 10g of degummed silk fibroin fiber and dissolve it in the lithium bromide aqueous solution, stir and dissolve at a temperature of 65°C, while stirring, drop 2.5mL (350mM) glycidyl methacrylate solution to perform methacrylation modification, stir for 6h to obtain a mixed solution, dialyze the mixed solution, and freeze-dry to obtain a sponge-like modified silk fibroin;

[0052] (2) Preparation of oxidized dextran

[0053] 2.5 g of dextran was added to 50 mL of deionized water to obtain a dextran solution, and then 5 mL (20% w / v) of sodium periodate solution was dropped into the dextran solution, stirred for 4 h at room temperature in the dark, and then 2 mL of ethylene glycol was added to stop the reaction, followed by dialysis and freeze-drying to obtain oxidized dextran, wherein the oxidized dextran has an oxidative substitution degree of 20%;

[0054] (3) 45 mL (10% w / v) of oxidized dextran solution was mixed with 10 mL (15% w / v) of modified silk fibroin solution, and then 10 mg 0.01% LAP (phenyl (2,4,6-trimethylbenzoyl) lithium phosphate) was added to mix to obtain a sol, and a photo-crosslinked double network hydrogel was obtained by ultraviolet light irradiation.

[0055] Example 4

[0056] (1) Preparation of modified silk fibroin

[0057] Take silkworm cocoons, cut them into pieces, add 2L of 5g / L Na2CO3 aqueous solution into the induction cooker, soak the cut silkworm cocoons in it, boil them slightly for 30 minutes, then soak and rinse them with a large amount of deionized water at least five times, repeat the above operation three times, wring them out, tear them into strips, and place them in a 37°C oven to dry to obtain degummed silk fibroin fibers.

[0058] Use a volumetric flask to make up the volume, prepare 50mL of 9M (40g) lithium bromide aqueous solution, take 10g of degummed silk fibroin fiber and dissolve it in the lithium bromide aqueous solution, stir and dissolve at a temperature of 65°C, while stirring, drop 2.5mL (350mM) glycidyl methacrylate solution to perform methacrylation modification, stir for 6h to obtain a mixed solution, dialyze the mixed solution, and freeze-dry to obtain a sponge-like modified silk fibroin;

[0059] (2) Preparation of oxidized dextran

[0060] 2.5 g of dextran was added to 50 mL of deionized water to obtain a dextran solution, and then 5 mL (40% w / v) of sodium periodate solution was dropped into the dextran solution, stirred for 4 h at room temperature in the dark, and then 2 mL of ethylene glycol was added to stop the reaction, followed by dialysis and freeze-drying to obtain oxidized dextran, wherein the oxidized dextran has an oxidative substitution degree of 40%;

[0061] (3) 5 mL (10% w / v) of oxidized dextran solution was mixed with 10 mL (15% w / v) of modified silk fibroin solution, and then 10 mg of 0.01% LAP (phenyl (2,4,6-trimethylbenzoyl) lithium phosphate) was added to mix to obtain a sol, and a photo-crosslinked double network hydrogel was obtained by ultraviolet light irradiation.

[0062] Example 5

[0063] (1) Preparation of modified silk fibroin

[0064] Take silkworm cocoons, cut them into pieces, add 2L of 5g / L Na2CO3 aqueous solution into the induction cooker, soak the cut silkworm cocoons in it, boil them slightly for 30 minutes, then soak and rinse them with a large amount of deionized water at least five times, repeat the above operation three times, wring them out, tear them into strips, and place them in a 37°C oven to dry to obtain degummed silk fibroin fibers.

[0065] Use a volumetric flask to make up the volume, prepare 50mL of 9M (40g) lithium bromide aqueous solution, take 10g of degummed silk fibroin fiber and dissolve it in the lithium bromide aqueous solution, stir and dissolve at a temperature of 65°C, while stirring, drop 2.5mL (350mM) glycidyl methacrylate solution to perform methacrylation modification, stir for 6h to obtain a mixed solution, dialyze the mixed solution, and freeze-dry to obtain a sponge-like modified silk fibroin;

[0066] (2) Preparation of oxidized dextran

[0067] 2.5 g of dextran was added to 50 mL of deionized water to obtain a dextran solution, and then 5 mL (40% w / v) of sodium periodate solution was dropped into the dextran solution, stirred for 4 h at room temperature in the dark, and then 2 mL of ethylene glycol was added to stop the reaction, followed by dialysis and freeze-drying to obtain oxidized dextran, wherein the oxidized dextran has an oxidative substitution degree of 40%;

[0068] (3) 15 mL (10% w / v) of oxidized dextran solution was mixed with 10 mL (15% w / v) of modified silk fibroin solution, and then 10 mg 0.01% LAP (phenyl (2,4,6-trimethylbenzoyl) lithium phosphate) was added to mix to obtain a sol, and a photo-crosslinked double network hydrogel was obtained by ultraviolet light irradiation.

[0069] Example 6

[0070] (1) Preparation of modified silk fibroin

[0071] Take silkworm cocoons, cut them into pieces, add 2L of 5g / L Na2CO3 aqueous solution into the induction cooker, soak the cut silkworm cocoons in it, boil them slightly for 30 minutes, then soak and rinse them with a large amount of deionized water at least five times, repeat the above operation three times, wring them out, tear them into strips, and place them in a 37°C oven to dry to obtain degummed silk fibroin fibers.

[0072] Use a volumetric flask to make up the volume, prepare 50mL of 9M (40g) lithium bromide aqueous solution, take 10g of degummed silk fibroin fiber and dissolve it in the lithium bromide aqueous solution, stir and dissolve at a temperature of 65°C, while stirring, drop 2.5mL (350mM) glycidyl methacrylate solution to perform methacrylation modification, stir for 6h to obtain a mixed solution, dialyze the mixed solution, and freeze-dry to obtain a sponge-like modified silk fibroin;

[0073] (2) Preparation of oxidized dextran

[0074] 2.5 g of dextran was added to 50 mL of deionized water to obtain a dextran solution, and then 5 mL (40% w / v) of sodium periodate solution was dropped into the dextran solution, stirred for 4 h at room temperature in the dark, and then 2 mL of ethylene glycol was added to stop the reaction, followed by dialysis and freeze-drying to obtain oxidized dextran, wherein the oxidized dextran has an oxidative substitution degree of 40%;

[0075] (3) 45 mL (10% w / v) of oxidized dextran solution was mixed with 10 mL (15% w / v) of modified silk fibroin solution, and then 10 mg 0.01% LAP (phenyl (2,4,6-trimethylbenzoyl) lithium phosphate) was added to mix to obtain a sol, and a photo-crosslinked double network hydrogel was obtained by ultraviolet light irradiation.

[0076] Comparative Example

[0077] This comparative example provides a method for preparing a silk fibroin hydrogel, the preparation method comprising the following steps:

[0078] (1) Degumming: adding silk to a sodium carbonate solution and heating it to obtain degummed silk;

[0079] (2) modification: dissolving the degummed silk in a lithium bromide solution, and then adding glycidyl methacrylate to react to obtain a reaction solution;

[0080] (3) Dialysis: dialyzing the reaction solution to obtain a supernatant;

[0081] (4) freeze-drying: freeze-drying the supernatant to obtain freeze-dried protein;

[0082] (5) Gelation: mixing the freeze-dried protein with a photoinitiator solution, and irradiating the freeze-dried protein solution with blue-violet light to obtain the silk fibroin hydrogel.

[0083] Effect verification

[0084] 1. State of photo-crosslinked double network hydrogel

[0085] The sol prepared in Example 1 was placed in a glass container and then irradiated with ultraviolet light. A sol-gel transition occurred and the fluidity of the solution disappeared. The container was inverted for 1 minute and there was no flow, indicating that a hydrogel was successfully formed. The results are as follows: Figure 1 shown.

[0086] 2. Observation of the morphology of photocrosslinked double network hydrogel

[0087] like Figure 2As shown, the photo-crosslinked double network hydrogel prepared in Example 1 and the silk fibroin hydrogel prepared in the comparative example were freeze-dried and placed in a dryer for 24 hours, and the surface morphology and porous structure of the two were observed using a scanning electron microscope. Figure 2 The left figure is the silk fibroin hydrogel prepared in the comparative example, and the right figure is the photo-crosslinked double network hydrogel prepared in Example 1. Figure 2 It can be seen that the hydrogel prepared in the comparative example is a single-layer grid structure, while the hydrogel prepared by introducing oxidized dextran in the present invention is a double-layer network structure, and the internal structure is a dense mesh structure, which is more dense.

[0088] 3. Self-healing and injectable properties testing of photocrosslinked double network hydrogels

[0089] (I) Self-healing performance test

[0090] like Figure 3 As shown, two hydrogels of the same shape and size were prepared by Example 1, and then the two hydrogels were dyed with rhodamine and methylene blue respectively, and the two dyed hydrogels were cut in half respectively, and then the two hydrogels of different colors were spliced ​​together after cutting in half. After 5 minutes, it was observed that the two hydrogels spliced ​​together were successfully healed without obvious gaps, and there was no breakage when stretched. The above results show that the silk fibroin hydrogel prepared by the present invention can effectively achieve self-healing.

[0091] (II) Injectability test

[0092] like Figure 4 As shown, the sol prepared in Example 1 is first sucked into a syringe, and an ultraviolet light source is used to irradiate the syringe so that the sol therein forms a hydrogel. After the hydrogel is formed, it is stained with rhodamine, and then the syringe needle is inserted below the liquid surface. While injecting, a photo is taken to observe the hydrogel. Figure 4 It can be observed that it can be easily injected and the injected hydrogel is complete and coherent without breaking or shattering, indicating that it has injectable properties.

[0093] 4. Hydrogel rheological properties test

[0094] (1) Rheological tests were performed using an AR 2000ex (TAinstrument) rheometer with a 25 mm stainless steel flat disc fixture and a fixture gap of 400 μm.

[0095] (2) The hydrogel prepared in Example 1 was added into a rheometer, and the rheological properties of the sample were measured within a time range of 0-500 s.

[0096] (3) Test and record the elastic modulus (storage modulus) of the hydrogel (G’ ) and viscous modulus (loss modulus) (G ” ) versus time with a frequency of 1 rad / s.

[0097] (4) The results are as follows Figure 5 As shown, from Figure 5 It can be seen that in the time period of 0-100s, when the pressure is 1%, the hydrogel storage modulus (G ’ ) is greater than the loss modulus (G ” ), indicating that the hydrogel was successfully formed, and the storage modulus was about 200 Pa, indicating that it had excellent mechanical properties and could meet the conventional requirements for dressings. In the 100-200s period, when the pressure was increased to 1200%, the hydrogel began to break, and at this time the storage modulus (G ’ ) is less than the loss modulus (G ” ), the hydrogel turned into a sol state, indicating that the hydrogel has a strong compressive resistance and will not break easily during use. In the period of 200-300s, when the pressure was returned to 1%, the hydrogel began to self-heal, and the storage modulus (G ’ ) recovers to about 200 pa and is greater than the loss modulus (G ” ), and returned to the gel state. In the time period of 300-400s, when the pressure was increased to 1200%, the hydrogel began to break and the hydrogel turned into a sol state. In the time period of 400-500s, when the pressure was returned to 1%, the hydrogel began to self-heal and returned to the gel state. The above tests show that the silk fibroin hydrogel prepared by the present invention has strong mechanical properties, is not easy to break when applied on skin wounds, and can heal quickly after breaking.

[0098] 5. Rheometer storage modulus and loss modulus test of dextran with different oxidation substitution degrees and silk fibroin mixed at different mass ratios

[0099] like Figure 6 As shown, the silk fibroin hydrogels prepared in Examples 1-6 were respectively put into a rheometer for testing. The model and test steps of the rheometer were the same as those in "IV. Test of Rheological Properties of Hydrogels". When the mass ratio of silk fibroin to dextran was the same, the storage modulus of dextran with a substitution degree of 20% was higher than that of dextran with a substitution degree of 40%, indicating that the optimal oxidation degree of dextran was 20%. When the oxidation degree of dextran was the same (all 20%), the hydrogel performance was best when the mass ratio of silk fibroin to dextran was 3:1, and the storage modulus was maintained at around 200 Pa. At the same time, the intersection of the storage modulus and the loss modulus was the largest, and the pressure was 1000%, indicating that the optimal mass ratio of silk fibroin to dextran was 3:1.

[0100] 6. Biocompatibility testing

[0101] The silk fibroin hydrogels prepared in Examples 1-3 were named hydrogel 1, hydrogel 2 and hydrogel 3, respectively, and used as test samples. The biocompatibility of the hydrogels was evaluated by measuring their hemolytic activity on human red blood cells.

[0102] like Figure 7 As shown, 200uL of each of hydrogel 1, hydrogel 2, and hydrogel 3 were added to 1.5mL EP tubes, and then 800μL of 8% human red blood cells were added to each tube. After incubation in a 37°C incubator for 1h, centrifugation (1200g) was performed, and the release degree of hemoglobin was observed by taking photos. Then, the supernatant was taken from each tube, and the OD490 was measured to quantitatively calculate the hemolysis rate. Figure 7 The hemolytic effect of each experimental group on human red blood cells is shown in Figure 2. Figure 7 It can be seen that after incubation with red blood cells, the hydrogel prepared by the present invention basically shows no hemolytic activity, does not cause red blood cell rupture, has no obvious hemolytic toxicity, and has good biocompatibility.

[0103] Although the present invention has been described using the above preferred embodiments, it is not intended to limit the scope of protection of the present invention. Any person skilled in the art who makes various changes and modifications to the above embodiments without departing from the spirit and scope of the present invention still fall within the scope of protection of the present invention.

Claims

1. A method for preparing a self-healing, injectable photo-crosslinked double network hydrogel, characterized in that: The steps include: (1) Preparation of modified silk fibroin The degummed silk fibroin fibers are dissolved in a lithium bromide aqueous solution, stirred and dissolved at a temperature of 65°C, and a glycidyl methacrylate solution is added dropwise while stirring to perform methacrylation modification, and stirred for 5 to 8 hours to obtain a mixed solution, and the mixed solution is dialyzed and freeze-dried to obtain a sponge-like modified silk fibroin; (2) Preparation of oxidized dextran Dextran is added to deionized water, and then sodium periodate solution is dripped into the dextran solution, stirred at room temperature in the dark for 3 to 6 hours, and then ethylene glycol is added to stop the reaction, followed by dialysis and freeze-drying to obtain oxidized dextran; (3) The oxidized dextran solution is mixed with the modified silk fibroin solution, and then a photoinitiator solution is added to obtain a sol, and a photo-crosslinked double network hydrogel is obtained by irradiating the sol with ultraviolet light.

2. The method for preparing the self-healing, injectable photo-crosslinked double network hydrogel according to claim 1, characterized in that: The mass ratio of the silk fibroin fiber to the glycidyl methacrylate solution is 10:

3.

3. The method for preparing the self-healing, injectable photo-crosslinked double network hydrogel according to claim 1, characterized in that: The mass ratio of the dextran to the sodium periodate solution is 2.5:

1.

4. The method for preparing the self-healing, injectable photo-crosslinked double network hydrogel according to claim 1, characterized in that: The mass ratio of the modified silk fibroin to oxidized dextran is 3: (0.5~9)。 5. The method for preparing the self-healing, injectable photo-crosslinked double network hydrogel according to claim 1, characterized in that: The oxidation substitution degree of the oxidized dextran is 20%.

6. The method for preparing the self-healing, injectable photo-crosslinked double network hydrogel according to claim 1, characterized in that: In the step (1), the concentration of the lithium bromide aqueous solution is 8 to 10 mol / L; the concentration of the glycidyl methacrylate solution is 300 to 400 mmol / L.

7. The method for preparing the self-healing, injectable photo-crosslinked double network hydrogel according to claim 1, characterized in that: In the step (2), the mass concentration of the sodium periodate solution is 20%.

8. The method for preparing the self-healing, injectable photo-crosslinked double network hydrogel according to claim 1, characterized in that: In the step (3), the mass volume concentration of the modified silk fibroin aqueous solution is 10-20%; the mass volume concentration of the oxidized dextran aqueous solution is 5-10%.

9. The method for preparing the self-healing, injectable photo-crosslinked double network hydrogel according to claim 1, characterized in that: In the step (3), the mass volume concentration of the photoinitiator solution is 0.1-0.2%.

10. A self-healing, injectable photo-crosslinked double network hydrogel, characterized in that: The method is described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • GelMA-oxidized dextran double-network hydrogel and preparation method thereof

    CN110951096A

  • Injectable antibacterial interpenetrating double-network hydrogel as well as preparation method and application thereof

    CN112300420A

  • Preparation method and application of photocuring dual-network hydrogel

    CN113773456A

  • Silk fibroin / hyaluronic acid composite hydrogel as well as preparation method and application thereof

    CN114524953A

  • Self-healing hydrogel and preparation method thereof

    CN117427214A

Cited By

  • Silk fibroin composite gel and preparation method thereof

    CN120501932A

  • Silk fibroin composite gel and preparation method thereof

    CN120501932B

  • Photo-crosslinking dual-network hydrogel for promoting skin wound healing and preparation method thereof

    CN121378801A